2000
DOI: 10.1073/pnas.200109597
|View full text |Cite
|
Sign up to set email alerts
|

High-affinity ouabain binding by a chimeric gastric H + ,K + -ATPase containing transmembrane hairpins M3-M4 and M5-M6 of the α 1 -subunit of rat Na + ,K + -ATPase

Abstract: Na ؉ ,K ؉ -ATPase and gastric H ؉ ,K ؉ -ATPase are two related enzymes that are responsible for active cation transport. Na ؉ ,K ؉ -ATPase activity is inhibited specifically by ouabain, whereas H ؉ ,K ؉ -ATPase is insensitive to this drug. Because it is not known which parts of the catalytic subunit of Na ؉ ,K ؉ -ATPase are responsible for ouabain binding, we prepared chimeras in which small parts of the ␣-subunit of H ؉ ,K ؉ -ATPase were replaced by their counterparts of the ␣1-subunit of rat Na ؉ ,K ؉ -ATPas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 38 publications
1
33
0
2
Order By: Relevance
“…The crystallographic data may, however, predict an arrangement of the ten α1-subunit helices within the plane of the lipid bilayer that is common to both enzymes. In a third approach, chimeras of individual Na/KATPase loop regions were inserted into either the skeletal muscle sarcoplasmic reticulum/ endoplasmic reticulum Ca 2+ -ATPase (SERCA1) [39,40] or the gastric H/K-ATPase [41,42]. The results suggest that M1-M2, M3-M4 and M5-M6 extracellular loops (see Figure 2) are important for ouabain sensitivity.…”
Section: The Ouabain Binding Site On the α1-subunitmentioning
confidence: 99%
“…The crystallographic data may, however, predict an arrangement of the ten α1-subunit helices within the plane of the lipid bilayer that is common to both enzymes. In a third approach, chimeras of individual Na/KATPase loop regions were inserted into either the skeletal muscle sarcoplasmic reticulum/ endoplasmic reticulum Ca 2+ -ATPase (SERCA1) [39,40] or the gastric H/K-ATPase [41,42]. The results suggest that M1-M2, M3-M4 and M5-M6 extracellular loops (see Figure 2) are important for ouabain sensitivity.…”
Section: The Ouabain Binding Site On the α1-subunitmentioning
confidence: 99%
“…The ATPase activity of chimera HN34/56 was 49% of that of the wild type H,K-ATPase at 10 M ATP, 3 mM KCl, and pH 6.0 (10). The ouabain binding level of Na,K-ATPase (QN) was 0.40 Ϯ 0.04 pmol/mg when 1 mM P i was present, whereas that of HN34/56 was 0.20 Ϯ 0.01 pmol/mg when 1 mM ATP was present (10). The ouabain binding level of H,K-ATPase was only 0.04 Ϯ 0.01 pmol/mg in the presence of 1 mM P i or ATP.…”
Section: Expression [ 3 H]ouabainmentioning
confidence: 99%
“…In a previous study, we demonstrated that replacement of the transmembrane hairpins M3-M4 and M5-M6 in H,KATPase by those of Na,K-ATPase results in the formation of a high affinity ouabain-binding site (10). In a follow-up study we showed that a chimera, in which only the M3-M4 hairpin and three amino acids of M5-M6 (Phe 783 , Thr 797 , and Asp 804 ) originate from Na,K-ATPase, binds ouabain with high affinity (11).…”
mentioning
confidence: 99%
“…The chimeras and mutants used in this study were: the rat Na,K-ATPase α 1 -subunit (wild type), the R111Q/ D122N mutant (QN) of this enzyme [10,11], the rat non-gastric H, K-ATPase α 2 -subunit [13] as well as its EGPLC mutant (D312E, S319G, A778P, I795L, F802C) [14]. Generation of the vectors containing the α 2 -subunit of rat non-gastric H,K-ATPase with the β 1 -subunit of rat Na,K-ATPase or the α 1 -subunit of rat Na,K-ATPase with the β 1 -subunit of sheep Na,K-ATPase that were suited for the baculovirus expression system, has been reported before [5,14].…”
Section: Methodsmentioning
confidence: 99%
“…In 2000, we surprisingly showed a high affinity for ouabain in a chimera that had, as basis, the gastric H,K-ATPase (α and β subunits) and in which the transmembrane segments M3/ M4 and M5/M6 of the α-subunit were replaced by those of Na,K-ATPase [11]. This chimera was expressed in insect cells using the baculovirus expression system.…”
Section: Introductionmentioning
confidence: 98%